Factors Associated With The Occurrence of Pulmonary Tuberculosis In The Working Area of Bulasat Public Health Center Mentawai Islands Regency, In 2025 - Sanjethro Sanjethro; Aisyah Jannatus Shabrina; Denny Christian Lukas (CV. Inara, 2025)
Background: According to the 2024 Global TB Report, tuberculosis remains one of the leading causes of death worldwide. Indonesia ranks second among the countries with the highest TB burden. The TB problem in Bulasat Public Health Center, Mentawai Islands Regency, is partly influenced by community behavioral factors, particularly among populations living in remote and island areas. Methods: This study is a quantitative research using a case-control design involving 60 community samples within the working area of Bulasat Public Health Center. The sampling technique used was non-probability purposive sampling. Results: The findings show a significant association between pulmonary TB occurrence and sex (p-value = 0.039; OR = 3.45), age (p-value = 0.018; OR = 4.3), education (p-value = 0.011; OR = 5.7), accessibility (p-value = 0.036; OR = 3.6), perception (p-value = 0.038; OR = 3.5), attitude (p-value = 0.018; OR = 4.3), and knowledge (p-value = 0.019; OR = 4.1). Knowledge was found to be the most dominant factor influencing TB incidence. Conclusion: This study indicates that TB incidence in the Bulasat Public Health Center working area is associated with sex, age, education, accessibility, perception, attitude, and knowledge. Knowledge is the most dominant associated factor. Strengthening health education, developing information media, and enhancing cross-sector collaboration are needed to improve community knowledge about TB and reduce the incidence rate.